(untitled) (Communications in Computational Physics, 2026)
In recent decades, gas-kinetic unified algorithm (GKUA) based on Boltzmann model equation has been proposed, which is suitable for the whole regimes gas flows. The original GKUA is designed for single-component gas flows. In this work, we extend GKUA to multi-component monatomic gas mixture flows based on the Andries-Aoki-Perthame (AAP) model. The algorithm are validated by the steady normal shock wave structure problem, the flow around two-dimensional circular cylinder and the pressure/temperature gradient driven microchannel flow problems. Simulation results are in good agreement with those obtained by other methods, which verifies the reliability of the proposed algorithm for the simulation of multi-component monatomic gas mixture. Then, taking the 25N attitude control engine two-dimensional profile as the object, the study of two-dimensional profile nozzle internal and external mixed flow problem is carried out, and the influences of the component concentration ratio and mass ratio on the molecular transport in the engine internal and external mixed flow field are discussed.